Getting it Right: Uganda’s Proposed National Health Insurance Scheme - Nabwowe, Angella; Mncwabe, Nokukhanya (My University, 2015)
Globally, the World Health Organization (WHO) has been pushing for universal health coverage. According to WHO, the goal of universal health coverage is to ensure that all people obtain the health services they need without suffering financial hardship by having to incur out of pocket expenses to pay for said services. Looking at the post 2015 health agenda, WHO notes that universal health coverage is a way of ensuring continued progress towards the current health Millennium Development Goals (MDGs), while also helping countries address the growing threat of non-communicable diseases, mental illness and injuries. The Ugandan Ministry of Health is currently awaiting a certificate of financial implication from the Ministry of Finance, Planning and Economic Development in order to proceed with the proposed National Health Insurance Bill 2012, which once adopted, will operationalise the National Health Insurance Scheme (NHIS). This is a commendable step towards the realization of the right to the highest attainable standard of physical and mental health in the country. However, as the process unfolds, the Initiative for Social and Economic Rights (ISER) deemed it fit to speak to a number of stakeholders to ensure representation of their priorities and concerns.